Alternating Current Electrohydrodynamics Induced Nanoshearing and Fluid Micromixing for Specific Capture of Cancer Cells. Issue 13 (23rd February 2014) - Vaidyanathan, Ramanathan; Rauf, Sakandar; Dray, Eloïse; Shiddiky, Muhammad J. A.; Trau, Matt
Abstract We report a new tuneable alternating current (ac) electrohydrodynamics (ac‐EHD) force referred to as "nanoshearing" which involves fluid flow generated within a few nanometers of an electrode surface. This force can be externally tuned via manipulating the applied ac‐EHD field strength. The ability to manipulate ac‐EHD induced forces and concomitant fluid micromixing can enhance fluid transport within the capture domain of the channel (e.g., transport of analytes and hence increase target–sensor interactions). This also provides a new capability to preferentially select strongly bound analytes over nonspecifically bound cells and molecules. To demonstrate the utility and versatility of nanoshearing phenomenon to specifically capture cancer cells, we present proof‐of‐concept data in lysed blood using two microfluidic devices containing a long array of asymmetric planar electrode pairs. Under the optimal experimental conditions, we achieved high capture efficiency (e.g., approximately 90 %; % RSD=2, n=3) with a 10‐fold reduction in nonspecific adsorption of non‐target cells for the detection of whole cells expressing Human Epidermal Growth Factor Receptor 2 (HER2). We believe that our ac‐EHD devices and the use of tuneable nanoshearing phenomenon may find relevance in a wide variety of biological and medical applications.